Comparative histochemistry and cell morphology of sapwood and heartwood of Gliricidia septium (Fabaceae) - Quintanar, Alejandra (1997)
Gliricidia septium (Jacq) Sted. (Fabaceae) shows remarkably high ratio heatwood to sapwood